2017
DOI: 10.1016/j.ydbio.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cis-acting regions control six6 expression during eye field and optic cup stages of eye formation

Abstract: The eye field transcription factor, Six6, is essential for both the early (specification and proliferative growth) phase of eye formation, as well as for normal retinal progenitor cell differentiation. While genomic regions driving six6 optic cup expression have been described, the sequences controlling eye field and optic vesicle expression are unknown. Two evolutionary conserved regions 5′ and a third 3′ to the six6 coding region were identified, and together they faithfully replicate the endogenous X. laevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Barson et al (2015) showed that a second conserved enhancer, necessary for six6 expression in the mouse forebrain (Lee et al, 2012) maps close to candidate SNP ss1868315338. Additional putative enhancers, with poorly characterized functions, are also located within our candidate region in other species (Conte et al, 2010; Ledford et al, 2017; Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Barson et al (2015) showed that a second conserved enhancer, necessary for six6 expression in the mouse forebrain (Lee et al, 2012) maps close to candidate SNP ss1868315338. Additional putative enhancers, with poorly characterized functions, are also located within our candidate region in other species (Conte et al, 2010; Ledford et al, 2017; Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Barson et al (2015) did not find any nonsynonymous mutations in the six6 coding region, and results indicate that the selective target could be a regulatory element for this gene. Studies in various species have identified multiple 5’ evolutionarily conserved enhancer elements which regulate six6 expression in different tissues and at different development stages (Conte et al, 2010; Ledford et al, 2017; Lee et al, 2012). Six6 regulation also involves at least one 3’ enhancer (Conte et al, 2010; Ledford et al, 2017), and may also be mediated by local chromatin structure (Gómez-Marín et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many putative six6 enhancer elements are located within our candidate region in other species. Several have directly been shown to regulate six6 expression in different tissues and at different developmental stages, while others remain poorly characterized (Conte et al., ; Ledford et al., ; Lee, Rizzoti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological expression of SIX6 has been described in eye development [ 24 ]. In this context SIX6 is regulated via defined enhancers and TFs neither of which are known to involve NKX3-1 or NKX3-2 [ 44 , 45 ]. During eye-development SIX6 sets the balance between proliferation and differentiation in the retina and suppresses specific non-lineage genes [ 33 , 46 ].…”
Section: Discussionmentioning
confidence: 99%